ANALISIS PEMBENTUKAN KARAKTER PESERTA DIDIK MELALUI PEMBELAJARAN OLAHRAGA - mardianto, heru; Chinta, Ira; Putra, Genta Dwi; Padli, Padli (Jurnal Tunas Pendidikan, 2024)
ABSTRACT Education throughout the world has the same goals and objectives. This includes helping students become smarter, helping them become better and have better character. This research uses a type of literacy research. Literacy research is a type of research carried out by in-depth study of books, literature, notes and various reports related to the problem to be discussed and solved. Education that embodies human activity in attitudes and actions, which are given personality content and orientation in accordance with human goals that is called sports education. Sports values are common to all individuals involved in sports, because sports values are able to shape human civilization and character. Individuals who are active in sports show higher self-confidence than teenagers who are not active in sports. The conclusions in this research show that the values contained in sports education can help build character in students. Keywords: Sports, Character, Education